Pengaruh current ratio (CR), Receivable turn over (RTO), dan Debt to equity ratio (DER) terhadap return on assets (ROA) pada perusahaan subsektor pedagangan besar dan perdagangan eceran yang tercatat dalam bursa efek indonesia (BEI) - Erica erica (Akuntansi Prima, 2021)
The objective of the study is to examine and analyze the effect of current ratio, receivable turnover and debt to equity ratio on return on assets in the large trading and retail trade subsector companies listed on the Indonesia Stock Exchange in 2013-2017. The research used a quantitative research method; this type of research is quantitative research using secondary data obtained from the Indonesia Stock Exchange. The research nature was to find out the relationship between variables. The research populations were all large trading and retail trading subsector companies listed on the Indonesia Stock Exchange consisting of 62 companies. The research samples were drawn by using a purposive sampling technique using certain criteria that the research samples consisted of 19 companies. The research data were analyzed by using multiple linear analysis, classic assumption tests including normality test, multicollinity test, autocorrelation test, and heterokedasticity test, as well as the F test and the T test. Partially, the result showed that the current ratio and receivable turnover positively and positively affected and significant on return on assets while the debt to equity ratio has a negative and significant effect on return on assets. The simultaneous testing showed that the current ratio, receivable turn over and debt to equity ratio affected return to assets. The results of the coefficient of determination showed that 62% of the variable return on assets can be explained by the variable current ratio, receivable turn over and debt to equity ratio.